Combining molecular patterns and clinical data for better immune checkpoint inhibitor prediction in metastatic urothelial carcinoma - Váradi, Melinda; Horváth, O.; Soós, E.; Csizmarik, A.; Németh, B.; Győrffy, B.; Kenessey, I.; Reis, H.; Koll, F.; Oláh, C.; Hadaschik, B.; Krafft, U.; et al. (Cancer immunology immunotherapy, 2025)
The therapeutic landscape of advanced urothelial carcinoma (UC) is evolving, making the prediction of immune checkpoint inhibitor (ICI) therapy efficacy crucial. Standalone biomarkers offer limited predictive value, necessitating integrative approaches combining clinicopathological, laboratory, and molecular factors to enhance accuracy. This study aimed to evaluate clinical and molecular factors, including the real-life performance of PD-L1 IHC, to improve treatment outcome prediction in ICI-treated UC patients, ultimately developing a more precise therapy selection model.
Online veröffentlicht: 12. November 2025
Gesehen am 29.01.2026